Adverse childhood experiences and perceived stress in early adulthood in the context of disadvantage. (September 2022) - Scorza, Pamela; Corbeil, Thomas; Wall, Melanie; Monk, Catherine; Suglia, Shakira; Wainberg, Milton; Alegria, Margarita; Canino, Glorisa; Bird, Hector; Duarte, Cristiane S.
Abstract: Background: Adverse childhood experiences (ACEs) may sensitize individuals to view situations in adulthood as more stressful, which may contribute to poor health outcomes. In populations facing disadvantage, ACEs may lead to the accumulation of stressors (stress proliferation or mediation hypothesis) throughout the life course. ACEs could also heighten perceived stress later in life due to its enduring impact (stress sensitization or effect modification hypothesis). Objective: We examine the associations between ACEs and perceived stress in early adulthood, considering concurrent life stressors, in a longitudinal cohort of Puerto Rican youth exposed to a high degree of disadvantage. Participants and setting: A community-based sample of 1626 Puerto Rican children living in disadvantaged contexts was followed longitudinally in the Boricua Youth Study from 2000 to 2017. Methods: ACEs were measured prospectively during childhood (<18 yrs), and life stressors and past year perceived stress were measured in early adulthood (EA; mean age = 23.4, sd 2.22). Causal mediation analysis tested ACEs' effects on EA perceived stress indirectly through life stressors including potential effect modification. Results: ACEs influenced perceived stress in EA (standardized total effect = 0.13, p  < .001) with 35% mediated by increased exposure to life stressors in EA due to ACEs. There was no evidence of increased sensitization to EA life stressors among those with higher ACEs exposure. Conclusions: ACEs contribute to perceived stress in EA, albeit with small effect, partially through accumulating effects of ongoing stressors, supporting the stress proliferation hypothesis. Policies aimed at reducing exposure to adversity from childhood to EA are needed to reduce the experience of ACEs and negative sequelae.